Evaluation Of The Implementation Of The Independent Curriculum Program At Smas Al Husna Tigaraksa - Qanitah Dzakiyyah Pariz; Matin Matin; Suryadi Suryadi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The Merdeka Curriculum is an education policy introduced in an effort to increase flexibility and creativity in the learning process. This study aims to evaluate the implementation of the Independent Curriculum Policy Program at Al Husna Tigaraksa Senior High School (SMAS) using the Context, Input, Process, Product (CIPP) Model. This research covers four dimensions of evaluation, namely context, input, process, and product, in order to provide a comprehensive picture of the impact and effectiveness of the independent curriculum policy at this school. The research method used both qualitative and quantitative approaches, including interviews with school officials, analysis of policy documents, classroom observations, and surveys of teachers, students, and parents. Evaluation instruments were developed based on the CIPP Model to measure the perception, academic achievement, and impact of the independent curriculum implementation. The evaluation results will provide in-depth insight into the understanding and implementation of the independent curriculum policy at SMAS Al Husna Tigaraksa. From the results of this study, the researchers found that the implementation of the independent curriculum at SMAS Al Husna is going well, the researchers checked the curriculum documents with the situation and the implementation of learning activities is appropriate, but there are still deeper adjustments in several aspects of the needs of students.